2019
DOI: 10.1002/acm2.12542
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prostate cancer prognostic Gleason grade group using zonal‐specific features extracted from biparametric MRI using a KNN classifier

Abstract: Purpose: To automatically assess the aggressiveness of prostate cancer (PCa) lesions using zonal-specific image features extracted from diffusion weighted imaging (DWI) and T2W MRI. Methods: Region of interest was extracted from DWI (peripheral zone) and T2W MRI (transitional zone and anterior fibromuscular stroma) around the center of 112 PCa lesions from 99 patients. Image histogram and texture features, 38 in total, were used together with a k-nearest neighbor classifier to classify lesions into their respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Since almost all clinically-significant lesions (i.e., 71 out of 73) have a Gleason grade group > 1, we can compare this value with the AUC of 88.8% obtained by our method for the G1 vs all task. Our experiments also confirm results of previous works showing the efficacy of radiomics for analyzing PCa images [40], [50]- [55]. In [56], entropy-based texture features extracted from gray-level co-occurrence matrix (GLCMs) were found to be related to GS, more specifically, that a higher GS is associated with a higher ADC entropy and low ADC energy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Since almost all clinically-significant lesions (i.e., 71 out of 73) have a Gleason grade group > 1, we can compare this value with the AUC of 88.8% obtained by our method for the G1 vs all task. Our experiments also confirm results of previous works showing the efficacy of radiomics for analyzing PCa images [40], [50]- [55]. In [56], entropy-based texture features extracted from gray-level co-occurrence matrix (GLCMs) were found to be related to GS, more specifically, that a higher GS is associated with a higher ADC entropy and low ADC energy.…”
Section: Discussionsupporting
confidence: 89%
“…Among these 112 lesions/findings, there were 36, 41, 19, 8, 8 tumors with GS ≤ 6 (G1), GS = 7 (3+4; G2), GS = 7 (4+3; G3), GS = 8 (4+4, 3+5, or 5+3; G4), and GS ≥ 9 (G5), respectively ( Table I). In the cohort of 99 patients (average age 65 years, range 42-78 years), 87 patients had one lesion, 11 patients had two, and a single patient had three [40]. Table II reports the number of layers in each of the 9 pretrained CNN architectures and their corresponding number of unique DEFs.…”
Section: A Characteristics Of the Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow diagram is depicted in Figure 1 . In total, 27 articles were eligible for inclusion in this review [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. From these, 13 studies reported enough information to perform a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is an effective model that is widely employed for data mining [ 15 ], and it functions effectively as a nonparametric model for classification and regression [ 16 ]. It is also commonly used in research on PCa [ 15 , 17 19 ].…”
Section: Methodsmentioning
confidence: 99%